Primary pre-service teachers’ self-efficacy beliefs in integrating gender approaches: relationship with demographic profiles - El Ouahabi, Fatima Zahra; Essaoudi, Hafida; Fattari, Amale; Hamdane, Karima; Abbassi, Siham; El Bouzaidi, Rachid Drissi; Chaiba, Abdellah (Frontiers in Education, 2025)
This study investigates the self-efficacy beliefs of Moroccan primary pre-service teachers in implementing gender-sensitive teaching practices. Drawing on data from 392 trainees across six Regional Centers for Education and Training Professions, the research used a mixed-methods approach combining a validated self-efficacy scale with focus group interviews. The study aimed to assess trainees’ confidence levels in gender knowledge, pedagogical implementation, and attitudes, focusing first on challenges faced by female trainers in Morocco and how these vary according to demographic characteristics. Findings reveal that trainees generally express moderate to high self-efficacy in applying gender-responsive pedagogy and fostering inclusive attitudes. However, a clear gap persists in their conceptual understanding of gender issues, indicating a need for stronger theoretical foundations. Female trainees consistently reported greater confidence in gender pedagogy than their male counterparts, while educational level, specialization, and year of training had minimal influence on self-efficacy beliefs. The results underscore the importance of integrating targeted gender content and practical strategies in teacher education. Focus group insights further suggest that trainees are eager to adopt inclusive practices but lack structured training and institutional support. This research offers timely insights into the current state of gender integration in Moroccan teacher training. It emphasizes the urgency of curriculum reforms that promote gender equity and highlights the role of teacher self-efficacy in driving inclusive educational transformation. Its significance lies in informing national strategies that aim to equip future Moroccan educators with the confidence and tools necessary to foster equitable and gender-responsive classrooms.